Financial literacy and economic growth: How Eastern Europe is doing? - Adina Teodora Pa÷sa; Xose Picatoste; Elena Mæadæalina Gherghina (Economics: The Open-Access, Open-Assessment Journal, 2022)
In this study, we aim to analyse financial literacy as a driver of financial wellbeing and economic growth in three of the most recent EU Member States, namely Romania, Bulgaria, and Croatia. Our particular interest in studying more in-depth these three countries is generated by their difficult pathway in the transition to the Euro and economic convergence on one side and by the limited analysis carried out so far in relation to them on the other side. Various studies indicate that financial literacy is associated with wealth accumulation, and financial education can help achieve economic growth. To conduct the empirical analysis, in this study, we have used primary data provided by the OECD for our specific research purposes. The raw data were collected in a survey carried out in 2019 in seven South Eastern European countries reaching over 1,000 respondents for each country. We used two-stage least-squares regression to test our hypothesis and cluster analysis for comparisons among countries. Conclusions of our research reveal the main differences between countries in terms of financial literacy and reverse causality between financial literacy and economic growth for the analysed countries. Finally, the study gives some insights into the future design of public policies on financial education in these countries.
Keywords: G53; F43; J40; 330; economic growth; financial literacy; labour market